2013
DOI: 10.1111/pace.12124
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Patient Radiation Dosage during Pediatric SVT Ablations Using an “ALARA” Radiation Reduction Protocol in the Modern Fluoroscopic Era

Abstract: An ALARA protocol for ablation of SVT reduced radiation to below levels previously reported for combined EAM/fluoro approaches. Success rates were excellent with no complications and without the costs of EAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…37 In particular, a combination of very low frame rates (2-3 frames per second), antiscatter grid removal and avoidance of magnification was found to produce an excellent dose reduction for EPS procedures. 38 It should be noted, however, that higher doses can be justified if it can be demonstrated that patient outcome is improved accordingly.…”
Section: 4mentioning
confidence: 98%
“…37 In particular, a combination of very low frame rates (2-3 frames per second), antiscatter grid removal and avoidance of magnification was found to produce an excellent dose reduction for EPS procedures. 38 It should be noted, however, that higher doses can be justified if it can be demonstrated that patient outcome is improved accordingly.…”
Section: 4mentioning
confidence: 98%
“…1823 Also the removal of the scatter grid, which resulted in poorer image quality, has been shown to reduce radiation by as much as two-fold. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies published in research literature have demonstrated that NMSs can confer the extra benefit of significantly reducing radiation exposure [10,14,32,33] during CA and also during paediatric electrophysiological procedures [9,13,24,25,26,30]. However, the use of NMSs during paediatric electrophysiological procedures is not a standard in many EP laboratories, and some colleagues are trying to reduce fluoroscopy exposure using low-dose fluoroscopy rather than utilizing NMSs [17,27,31].…”
Section: Introductionmentioning
confidence: 93%